The influence of financial literacy, digital literacy, and income on investment decisions with religiosity as an intervening variable among Muslim millennials in Yogyakarta - Nugraha, Amri Satria; Sutrisno, Sutrisno (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2024)
This research aims to examine the influence of digital literacy, financial literacy, and income variables on investment decisions with religiosity as an intervening in the Muslim millennial generation in Yogyakarta The approach used in this research is quantitative. The sample used in this research was 185 respondents. Research data was obtained from the results of filling out the questionnaire and then analyzed using SEM analysis techniques with the help of the SEM AMOS program. The results of this research show that: (1) Financial literacy directly has a positive and significant effect on investment decisions; (2) Digital literacy directly has a positive and significant effect on investment decisions; (3) Income directly has a positive and significant effect on investment decisions; (4) religiosity directly has a positive and significant effect on investment decisions; (5) Religiosity can mediate financial literacy on investment decisions; (6) Religiosity cannot mediate digital literacy on investment decisions; (7) Religiosity cannot mediate income on investment decisions.